Affective neuroscience personality differences between medical school students and engineering school students - Hoşgören Alıcı, Yasemin; Hasanli, Jamal; Ceran, Selvi (Acta Medica, 2023)
Objective: Medical and engineering faculty students both choose their majors from the field of science. But the educational process differs between the two majors. In this study we aimed to investigate the personality traits that might affect this preference. Affective Neuroscience Personality Scales (ANPS) could be particularly useful in studying the traits linked to the affective formation of the individual. Materials and Methods: We prepared an online survey form collecting the sociodemographic and clinical data and the ANPS. We investigated the relationship between affective personality traits determined by the ANPS and the selection of the major. Also, we examined the affective personality traits that may influence the development of psychiatric illness in our sample. Results: 219 medical students and 222 engineering students participated the study. Participants’ ages ranged between 18 and 33 (Median=21; IQR=3). Among participants 60,5% were female, 34,7% has a psychiatric illness, 11,3 % had a chronic illness, and 16,8% has a family history of psychiatric illness. ANPS total and subscale scores weren’t different between the groups. The SADNESS subscale scores were associated with the occurrence of the psychiatric illness. Conclusion: The lack of difference between the two groups may indicate that affective personality profile is not a decisive factor in this choice. Our limitations are the small sample size, the lack of representation of our sample and the scarcity of data about other factors that might affect this preference. SADNESS was associated with psychiatric disorders in both groups.